СТАНОВИЩЕ СІЛЬСЬКОЇ ПОШТИ В УКРАЇНІ В 40–60-ті РОКИ ХІХ ст. (Zaporizhzhia Historical Review, 2021)
Based on the sources materials in the article the rural post’ actuvity in Ukraine before the agrarian end Zemstvo reform is examined. The specially attention is given to the Russian post workers’ projects as for improvemement of the post’ means of communication between villagers in the Ukrainian lands.